(3JGQjN GdLRGFQ GdYGe GdLRA GdQGHY (B:s (3ef(B1246(3g(B/1830(3e Edi(B1253(3g(B/1837(3e (B/s - (3GdLjdGdj,YHO GdQMeGf Hf eMeO s ((3GdLRGFQ (B:s (3TQcI OGQ GdCeI ddWHGYI h GdfTQ h GdJhRjY ,s, 2014)
(3jTJed Ydi GjLGR hGaj eaUd dJGQjN GdbWQ GdLRGFQj aj LejY GWhGQg h MQcJg GdSjGSjI hGdGLJeGYjI h GdKbGajI h GdOjfjI h GdCOHjI h GdafjI h GdGbJUGOjI h GdYeQGfjI h GdUfGYjI eY JQGLe fNHI ef GdYHbQjjf h CUMGH GdbQGFM ef eTGgjQ GdLRGFQjjf efP GbOe GdYUhQ Edi GdBf (B.s
Keywords: (3JGQjN GdLRGFQs; (3JGQjN GdLRGFQ GdYGe s